2005
DOI: 10.1007/s00428-005-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

In situ glomerular expression of activated NF-κB in human lupus nephritis and other non-proliferative proteinuric glomerulopathy

Abstract: Nuclear Factor-kappaB (NF-kappaB) has been suggested to play a role in the cellular and molecular mechanisms underlying glomerular injury. We investigated the potential role of NF-kappaB activation in the pathogenesis of glomerular injury in 31 patients with class III-V lupus nephritis (LN), 14 patients with non-proliferative proteinuric glomerulopathy and six normal controls. The expression of NF-kappaB subunits p65 and p50, and the NF-kappaB regulated proinflammatory mediators tumor necrosis factor-alpha (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 50 publications
0
70
1
Order By: Relevance
“…Contrary to us, Zheng et al showed a positive correlation of glomerular NF-κB also in the non-proliferative group. However, in this study glomerular NF-κB immunoexpression was confined only to podocytes [1]. Our observations may suggest different mechanisms of proteinuria in proliferative and non-proliferative glomerulopathies.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Contrary to us, Zheng et al showed a positive correlation of glomerular NF-κB also in the non-proliferative group. However, in this study glomerular NF-κB immunoexpression was confined only to podocytes [1]. Our observations may suggest different mechanisms of proteinuria in proliferative and non-proliferative glomerulopathies.…”
Section: Discussioncontrasting
confidence: 58%
“…In the present study we revealed that glomerular immunoexpression of NF-κB was significantly increased in PG proteinuric patients as compared to the NPG group and controls. NF-κB activation has been observed in several experimental and human glomerular diseases [1,15,16]. Sakurai et al noted increased activation of NF-κB in rat glomeruli shortly after nephrotoxic serum administration and the development of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, NF-B activates in macrophages and glomerular (including podocytes in proteinuric diseases) and tubular parenchymal cells and correlates with parameters of severity of disease such as proteinuria or inflammation. 59,[61][62][63][64][65] These data have been interpreted as supportive for the role of NF-B in promoting inflammation; however, inflammation itself will promote NF-B activation, and because these data are descriptive, the precise role of the various NF-B complexes in human kidney injury remains uncertain. Functional evidence of NF-B activation has been obtained by transcriptomics-based pathway mapping 66 ; in progressive diabetic nephropathy, there is upregulation of 54 of 138 known NF-B targets with special enrichment in NF-B/IRFF module target genes.…”
Section: Nf-b Activation In Experimental and Human Renal Diseasementioning
confidence: 99%